1992
DOI: 10.1017/s0950268800050512
|View full text |Cite
|
Sign up to set email alerts
|

Laboratory diagnosis ofMycoplasma pneumoniaeinfection. 4. Antigen capture and PCR-gene amplification for detection of the mycoplasma: problems of clinical correlation

Abstract: Direct detection assays for Mycoplasma pneumoniae were established by PCR amplification of short sequences within the foot protein/adhesin (P1) gene and the 16S ribosomal RNA gene. Specificity and sensitivity was excellent, no hybridization was observed with M. genitalium and other human Mycoplasma species. In nose and throat washings from subjects with respiratory infection a pattern of high counts (c.f.u./ml) of M. pneumoniae (deduced from the amount of amplified PCR product), and a positive antigen capture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
49
0
9

Year Published

1995
1995
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(58 citation statements)
references
References 23 publications
0
49
0
9
Order By: Relevance
“…For instance, Loens et al suggested that the P1 adhesin gene may be more sensitive than the 16S rRNA one [13]. Two independent researchers, nevertheless, showed that the amplification of the 16S rRNA gene was more sensitive for the detection of M. pneumoniae because more positive samples were found by 16S rDNA PCR than by a PCR with the P1 gene [14,15]. The main reason for the ambivalent conclusions is that the researchers detected the DNA directly from clinical samples, rather than a standard strain DNA of M. pneumonia, to compare the sensitivity of 16S rDNA PCR with P1 gene PCR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, Loens et al suggested that the P1 adhesin gene may be more sensitive than the 16S rRNA one [13]. Two independent researchers, nevertheless, showed that the amplification of the 16S rRNA gene was more sensitive for the detection of M. pneumoniae because more positive samples were found by 16S rDNA PCR than by a PCR with the P1 gene [14,15]. The main reason for the ambivalent conclusions is that the researchers detected the DNA directly from clinical samples, rather than a standard strain DNA of M. pneumonia, to compare the sensitivity of 16S rDNA PCR with P1 gene PCR.…”
Section: Discussionmentioning
confidence: 99%
“…Both the P1 adhesin gene and 16S rRNA gene have been utilized widely in PCR techniques as the targets for detection of M. pneumoniae [13][14][15]. The P1 adhesin gene is an intriguing target gene for PCR because of its repetitive nature within the genome [14].…”
Section: Introductionmentioning
confidence: 99%
“…Aunque ambos estudios incluyeron un bajo número de pacientes, sería importante confirmar estos hallazgos 6,8 . La amplificación del ADN ha demostrado ser una técnica sensible para el diagnóstico de infección por M. pneumoniae en niños, pudiendo proporcionar los resultados dentro de 24 horas 5,[8][9][10][11][12] . Ha demostrado ser también útil para el diagnósti-co de infecciones por M. pneumoniae en niños inmunocomprometidos y en lactantes bajo 12 meses de edad, en los cuales la respuesta inmune humoral a este microorganismo es menor 8 .…”
Section: Discussionunclassified
“…Por otra parte, la especificidad de la detección de IgM mediante ELISA varía ampliamente entre 25 y 90%, dependiendo del kit comercial utilizado 3,4 . La amplificación del ADN mediante RPC ha sido señalada en algunos estudios como una alternativa sensible y específica para la detección de M. pneumoniae [8][9][10][11][12][13][14] . No obstante, se ha informado portación y persistencia de este microorganismo en la faringe luego de finalizado un cuadro respiratorio, lo que podría limitar la utilidad de esta técnica [1][2][8][9][10]15 .…”
Section: Introductionunclassified
See 1 more Smart Citation